Blockchain Technology Enabled Traceability Framework: Food Supply Chain Perspective - Ghode, Dnyaneshwar J.; Wagire, Aniruddha A.; Dwaramwar, Pravin A.; Khobragade, Rajesh H. (Journal of Graphic Era University, 2023)
In the global market, consumers have expectations of good quality food products. To provide flawless food products, traceability has become dominant in a complex food supply chain (SC) network. Stakeholders of the food SC hesitate to share their data with each other, as they have different business strategies. Blockchain Technology (BCT) brings all the parties of food SC on single platform to improve interorganizational trust. The implementation of BCT in food SC offers the traceability of products. This paper proposes a framework for traceability of products in food SC using BCT that offers the consumers to trace the origin of the food products. Blockchain enhances the food traceability, minimize the data tampering, and improves data transparency in food SC. BCT enabled food SC framework has been tested using case study of rice SC and found the enhancement in traceability.